Genetic diversity of Rhizoctonia solani isolates (Kuhn) from pepper in Mexico - Montero-Tavera Víctor; Guerrero-Aguilar, Brenda Zulema; Anaya-López José Luis; Martínez-Martínez Talina Olivia; Olvera Lorenzo, Guevara-; González-Chavira Mario Martín (Revista Mexicana de Ciencias Agrícolas, 2018)
One of the major constraints for the production of pepper are pathogenic fungi causing diseases known as "pepper blight" or "damping off". This disease can be devastating when weather conditions are favorable for the pathogen. Although different means of control (chemical and cultural) have benn used but none has been successful. An alternative to control is to produce resistant germplasm, however in order to establish an effective breeding program is necessary to know the distribution and genetic diversity of the pathogens involved, particularly Rhizoctonia solani, which by its ubiquity represents a potential danger in all producing areas. Thus, the objective was to characterize R. solani in North Central area from Mexico and determine its genetic diversity. To achieve with this goal are considered the states of Chihuahua, Durango, Zacatecas, San Luis Potosi, Colima, Queretaro and Guanajuato where in 2009 were collected adult plants of pepper with pepper blight symptoms, the fungus was isolated and found an incidence of 33%, finding it in both stem and root. Mycelial cells were multinucleated, a characteristic from pathogenic strains. The anastomosis testing showed that in Mexico are present the groups GA4, GA-2.1, GA-IIB, GA-2IV, GA7, GA11, GA12 and GA13. The genetic diversity of this fungus was very high, so that the relationships demonstrated by the construction of dendrogram show no homogeneous trends so as the main groups formed contain elements of all states.